Heterogeneity of the Impact of Geopolitical Events on Energy Trade: An Empirical Study Based on Regression Discontinuity Design - Liu, Yanqiong; Yu, Liang; Yang, Cunyi; Li, Zhenghui (Frontiers in Environmental Science, 2021)
In the context of intensifying global geopolitical disputes and trade frictions, the relationship between geopolitics and energy trade has attracted extensive attention from scholars. The complexity of geopolitical risks mainly comes from the diversity of geopolitical events, which directly leads to the different responses of energy trade in the face of geopolitical risks. The purpose of this paper is to analyze the heterogeneity of the impact of geopolitical events on energy trade based on the difference of event types. This paper uses Regression Discontinuity Design (RDD) to simulate a quasi-natural experiment. Based on the monthly data and the Geopolitical Risk index (GPR index) of 17 emerging economies from 2000 to 2020, the empirical analysis can be concluded as follows: Wars and conflicts events lead to the increase of energy trade volume; terrorist attacks have no significant impact on energy trade; international tension can cause the decline in energy trade. Additional analysis shows that the impact of geopolitical events on energy trade in emerging economies is concentrated on the demand side, and the demand is severely inelastic.